The Comparative Economics of Knowledge Economy in Africa: Policy Benchmarks, Syndromes and Implications - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2015)
The paper complements the scarce literature on knowledge economy (KE) in Africa by comparing KE dynamics within Africa in order to assess best and worst performers based on fundamental characteristics of the continent's development. The five dimensions of the World Bank's knowledge economy index (KEI) are employed, notably: education, information and communication technology, innovation and, economic incentives and institutional regime. The empirical evidence is based on a five-step novel approach with data from 53 African countries for the period 1996-2010. Limitations of the beta catch-up approach are complemented with the sigma convergence strategy. Based on the determined fundamental characteristics, computed dynamic benchmarks, policy syndromes and syndrome free scenarios we establish that: Landlocked, Low-income, Conflict-affected, sub-Saharan African, Non-oil-exporting and French civil law countries are generally more predisposed to lower levels of KE whereas; English common-law, Notlandlocked, Conflict-free, North African and middle-income countries are characteristics that predispose certain nations to higher KE. Broad and specific policy implications are discussed in detail.
Keywords: O10; O30; O38; O55; O57; 330; Knowledge economy; Benchmarks; Policy syndromes; Catch-up; Africa